The relationship between executive compensation incentives and audit fees: Chinese listed companies - FAN, BOWEN (2022)
This dissertation examines the relationship between audit fees and three forms of executive compensation in the Chinese market: equity compensation, cash compensation, and perquisites (perks). A sample of 13,364 firm-year observations of listed companies in Shanghai and Shenzhen from 2016 to 2020 is used to test the research question. Ordinary least squares regression (OLS) controlling for industry and year fixed effects with heteroskedasticity-robust standard errors are used to ensure unbiased results. This dissertation found that the equity-based compensation of executives of Chinese companies does not significantly impact audit fees. This is probably due to the low ratio of equity-based compensation neither effectively aligning shareholders and managers nor inducing them to perform opportunistic behaviours. In contrast, the level of executive cash compensation and the perks of executives have a significant positive impact on audit fees. Furthermore, some properties of the firm, specifically the level of earnings management, audit size, firm size, profitability, and CEO duality, can also have a prominent effect on audit fees. However, due to the unique regulatory requirements of China, independent boards of Chinese companies are found not to have a substantial influence on audit fees, which is different from the findings of other studies.